هەڵسەنگاندنی ڕۆڵی ئاووهەوا لە بەرهەمهێنانی بەروبومی گەنم و جۆ لە قەزای کەلار - محمد, هاورێ ياسين; احمد, شؤخان محمد; مه, سروه جلال حه (Sulaimani Journal for Humanities, 2023)
Agricultural production. So, determining the need of any agricultural product to the elements of climate is parallel to the pinpointing of the climate of the area at which a specific product is cultivated. This leaves great impact on the extend of success or failure of the process producing and agriculture products and its economic dimension and use, especially as much as the wheat and barley are concerned, the two kinds of cereals that retain an economic importance. The current research paper aims at guessing the climate elements (sun light, temperature, humidity and wind) in the district of Kalar and how far they are line with (harmonious) the climate requirements of the wheat and barley .However, it seeks to conduct a scientific analysis so that it can determine the essence and extent of the relationship between the climate requirements and producing the two foresaid products , namely , wheat and barley in kalar district, to raise their amount and abundance. So as to steer the research paper to its goals, we have divided it in to two axes. The first one is pertaining to introducing the two said products and pinpointing their climate requirements along with the general climate of the area, i.e. kalar. Whereas the second axis is dealing with conducting a statistical analyze for the relationship between climate elements and the abundance of those two cereals The research paper depends on climate data and some data related to the areas cultivated with those two cereals and both their production and abundance between the years (2004- 2021) depending on the subjective method and the quantitative analyse, Pearson correlation and simple liner regression, and expectation of production by using statistical (SPSS) program. The research paper has come to some conclusions , on top of them is the increase of (1 ml) rain in march which leads to the increase of wheat in an amount estimated in (40.5 kg/ dunam) and the increase of barley in (6.4 kg /dunam).